2015
DOI: 10.3389/fpsyg.2015.01662
|View full text |Cite
|
Sign up to set email alerts
|

Neural processing of emotions in traumatized children treated with Eye Movement Desensitization and Reprocessing therapy: a hdEEG study

Abstract: Eye Movement Desensitization and Reprocessing (EMDR) therapy has been proven efficacious in restoring affective regulation in post-traumatic stress disorder (PTSD) patients. However, its effectiveness on emotion processing in children with complex trauma has yet to be explored. High density electroencephalography (hdEEG) was used to investigate the effects of EMDR on brain responses to adults’ emotions on children with histories of early maltreatment. Ten school-aged children were examined before (T0) and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Moreover, different age groups ranging from infants [132,143,169], children [6,43,75,84,89,103,125,126,[128][129][130]140,183,184,[210][211][212][213], adolescents [59,65,70,135,139], and elderly [105,214] in different experiments were considered as study samples. Some studies were conducted on a single gender, such as those investigating women's emotions during motherhood and parental status [133,134,164] and a study of men [215].…”
Section: Mahnobmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different age groups ranging from infants [132,143,169], children [6,43,75,84,89,103,125,126,[128][129][130]140,183,184,[210][211][212][213], adolescents [59,65,70,135,139], and elderly [105,214] in different experiments were considered as study samples. Some studies were conducted on a single gender, such as those investigating women's emotions during motherhood and parental status [133,134,164] and a study of men [215].…”
Section: Mahnobmentioning
confidence: 99%
“…Other medical cases include autism [6,21,75,140,212,213], bipolar disorder [124,145], epilepsy [230,234,235], attention-deficit/hyperactivity disorder [103,165], bulimia nervosa [33,168], borderline personality disorder [167], pervasive developmental disorder [81], and eye movement desensitization and reprocessing [125].…”
Section: Othermentioning
confidence: 99%
“…Several neuroimaging investigations have demonstrated the effect of EMDR on cortical and sub-cortical regions involved in PTSD, depicting a clear association between disappearance of symptoms and the normalization of brain changes ( Lansing et al, 2005 ; Pagani et al, 2007 , 2012 , 2015 ; Nardo et al, 2010 ; Landin-Romero et al, 2013 ; Trentini et al, 2015 ; Laugharne et al, 2016 ; for review see Pagani et al, 2013 ). Whole session monitoring of cortical activations by EEG made EMDR the first psychotherapy in which neurobiological correlates have been depicted in real time ( Pagani et al, 2011 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study using a modified oddball paradigm containing auditory standard, target, and novel tones, showed decreased P3a component of event-related potentials after EMDR, suggesting reduced alertness and de-arousal upon treatment (Lamprecht et al, 2004). Two other EEG studies from the same lab, showed a shift from the medial prefrontal cortex and fronto-temporal activity during EMs in the first EMDR session, toward more posterior associative regions in the last session, that correlated with symptom improvement (Pagani et al, 2015; Trentini et al, 2015). However, these EEG studies recorded brain activity only during EMs and not after the intervention when—if successful—the memories lost vividness and emotionality.…”
mentioning
confidence: 91%